Workers' Exposure to Indium Compounds at the Electronics Industry in Republic of Korea - Gwangyong Yi; Jeeyeon Jeong; Yasung Bae; Jungah Shin; Hyelan Ma; Naroo Lee; Seung-Hyun Park; Dooyong Park (Elsevier, 2021)
Objectives: The aim of this study was to provide baseline data for the assessment of exposure to indium and to prevent adverse health effects among workers engaged in the electronics and related industries in Republic of Korea. Methods: Total (n = 369) and respirable (n = 384) indium concentrations were monitored using personal air sampling in workers at the following 19 workplaces: six sputtering target manufacturing companies, four manufacturing companies of panel displays, two companies engaged in cleaning of sputtering components, two companies dedicated to the cleaning of sputtering target, and five indium recycling companies. Results: The level of exposure to total indium ranged from 0.9 to 609.3 μg/m3 for the sputtering target companies; from 0.2 to 2,782.0 μg/m3 for the panel display companies and from 0.5 to 2,089.9 μg/m3 for the indium recycling companies. The level of exposure to respirable indium was in the range of 0.02 to 448.6 μg/m3 for the sputtering target companies; 0.01 to 419.5 μg/m3 for the panel display companies; and 0.5 to 436.3 μg/m3 for the indium recycling companies. The indium recycling companies had the most samples exceeding the exposure standard for indium, followed by sputtering target companies and panel display companies. Conclusions: The main finding from this exposure assessment is that many workers who handle indium compounds in the electronics industry are exposed to indium levels that exceed the exposure standards for indium. Hence, it is necessary to continuously monitor the indium exposure of this workforce and take measures to reduce its exposure levels.